Diurnal changes in transcript and metabolite levels during the iron deficiency response of rice - Selby-Pham, Jamie; Lutz, Adrian; Moreno-Moyano; Laura T.; Boughton, Berin, A.; Roessner, Ute; Johnson, Alexander A. T. (Springer, 2017)
Rice (Oryza sativa L.) is highly susceptible to iron (Fe) deficiency due to low secretion levels of the mugineic acid (MA) family phytosiderophore (PS) 2′-deoxymugineic acid (DMA) into the rhizosphere. The low levels of DMA secreted by rice have proved challenging to measure and, therefore, the pattern of DMA secretion under Fe deficiency has been less extensively studied relative to other graminaceous monocot species that secrete high levels of PS, such as barley (Hordeum vulgare L.). Gene expression and metabolite analyses were used to characterise diurnal changes occurring during the Fe deficiency response of rice. Iron deficiency inducible genes involved in root DMA biosynthesis and secretion followed a diurnal pattern with peak induction occurring 3–5 h after the onset of light; a result consistent with that of other Strategy II plant species such as barley and wheat. Furthermore, triple quadrupole mass spectrometry identified 3–5 h after the onset of light as peak time of DMA secretion from Fe-deficient rice roots. Metabolite profiling identified accumulation of amines associated with metal chelation, metal translocation and plant oxidative stress responses occurring with peak induction 10–12 h after the onset of light. The results of this study confirmed that rice shares a similar peak time of Fe deficiency associated induction of DMA secretion compared to other Strategy II plant species but has less prominent daily fluctuations of DMA secretion. It also revealed metabolic changes associated with the remediation of Fe deficiency and mitigation of damage from resulting stress in rice roots. This study complements previous studies on the genetic changes in response to Fe deficiency in rice and constitutes an important advance towards our understanding of the molecular mechanisms underlying the rice Fe deficiency response.